« Artisan, ça veut tout et rien dire » - Quelle lutte des classes dans la pêche bretonne ? - Fabien Clouette (Éditions en environnement VertigO, 2021)
The Breton fishing industry is often considered homogeneous, even though it conceals power relations that reflect a diversity of company sizes, economic and political interests and ecological sensitivities. This article is based upon the hypothesis of a particular class struggle in the sector, opposing the large corporations that concentrate capital and fishing rights not only to their workers on the deep-sea decks, but also to small-scale artisanal fishermen. Independent sailors and industrial deckhands have in common their subalternity towards these industrial corporations, as well as the search for an agency that is often expressed infra-politically. The article aims at deconstructing the naturalization of power relations, and analysing its effects.